Arah Kebijakan Pengawasan terhadap Perbankan Syariah dalam Sistem Perbankan Nasional di Indonesia - Andrew Shandy Utama (Volksgeist: Jurnal Ilmu Hukum dan Konstitusi, 2020)
This research aims to explain the direction of policy regarding supervision of Islamic banking in the banking system in Indonesia. The method used in this research is normative legal research using the statutory approach. The results of this research explain that the policy regarding supervision of Islamic banking in the national banking system in Indonesia is headed toward an independent direction. In Law Number 7 of 1992 and Law Number 10 of 1998, it is stated that supervision of Islamic banking is done by Bank Indonesia as the central bank. Based on Law Number 21 of 2008, supervision of Islamic banking is strengthened by not only being supervised by Bank Indonesia, but also by the National Sharia Council of the Majelis Ulama Indonesia by placing Sharia Supervisory Councils in each Islamic bank. After the ratification of Law Number 21 of 2011, supervision of Islamic banking moved from Bank Indonesia to an independent institution called the Financial Services Authority.